Assessment of Growth Factors, Cytokines, and Cellular Markers in Saliva of Patients with Trigeminal Neuralgia - Shankargouda Patil; Luca Testarelli (Molecules, 2021)
We proposed to perform a comparative analysis of growth factors, cytokines, and chemokine receptors on the salivary cells in the saliva obtained from trigeminal neuralgia (TN) and normal subjects. Saliva was collected from TN and healthy subjects. Salivary cells were isolated by centrifugation. The expression of the cell surface marker was analyzed by flow cytometry. A cytometric bead array was done to measure the levels of cytokines and growth factors on the flow cytometer. Saliva from TN subjects showed lower growth factor levels of Angiopoietin-2, bFGF, HGF, SCF, TGF-α, and VEGF and higher cytokine levels of IL-1β, TNF-α, CCL2, IL-17A, IL-6, and CXCL8, as well as higher expression levels of chemokine receptors CCR1 (CD191), CR3 (CD11b), CCR2 (CD192), CXCR5 (CD185), and CCR5 (CD196) in the cells from TN saliva. A certain set of cytokines and growth factors in the saliva, as well as chemokine receptors on salivary cells, could be a useful tool in the diagnostics and prognostics of trigeminal neuralgia. Trigeminal neuralgia is one of the significant pathological conditions in the class of chronic diseases around the world. Many targeted approaches are being tried by various research groups to utilize the information of the inflammatory microenvironment to resolve the pathology of chronic TN.